Resistance induction to root rot in papaya by biotic and abiotic elicitors - Tavares, Giltembergue Macedo (2010)
The objective of this work was to evaluate the potential use of biotic and abiotic elicitors of resistance in the reduction of root rot in papaya. Papaya seedlings were sprayed with the fosetil-Al and metalaxyl and Mancozeb (2 g L-1) fungicides, with the potassium phosphite (2.5 and 5 mL L-1), salicylic acid 0.15 e 0.30%, Reforce (commercial product) + salicylic acid 5%, acibenzolar-S-methyl (ASM) (0.15 and 0.30 g L-1) abiotic elicitors, and with the Saccharomyces cerevisiae (3 and 6 mL L-1) biotic elicitor, applied three and six days before the inoculation with 1 mL of 105 zoospores mL-1 suspension of Phytophthora palmivora. All treatments were effective in controlling papaya root rot in comparison with the control, except for the Reforce + salicylic acid 5% (3 mL L-1) treatment applied six days before inoculation. The treatments with the ASM elicitor, except for the 0.15 g L-1 dosage applied six days before inoculation, had control levels similar to those of the metalaxyl and Mancozeb fungicide. Plants sprayed with ASM presented increased peroxidase and beta-1,3-glucanase activity and higher lignin content than the control. However, these treatments had no effect on chitinase activity. ASM is a potential elicitor for resistance to P. palmivora in papaya.